Reinfusion of highly purified CD133+ bone marrow-derived stem/progenitor cells in patients with end-stage liver disease: A phase I clinical trial. Issue 12 (December 2015) - Andreone, Pietro; Catani, Lucia; Margini, Cristina; Brodosi, Lucia; Lorenzini, Stefania; Sollazzo, Daria; Nicolini, Benedetta; Giordano, Rosaria; Montemurro, Tiziana; Rizzi, Simonetta; Dan, Elisa; Giudice, Valeria; et al.
Abstract: Background: Bone marrow stem/progenitor cells seem to be effective in liver regeneration after tissue injury. Aim: To evaluate the feasibility and safety of the mobilization and reinfusion of CD133 + stem/progenitor cells in patients with end-stage liver disease. Methods: Autologous CD133 + stem/progenitor cells, mobilized with granulocyte-colony stimulating factor, were collected by leukapheresis and reinfused at increasing doses through the hepatic artery starting from 5 × 10 4 /kg up to 1 × 10 6 /kg. Results: 16 subjects with Model for End-stage Liver Disease (MELD) score between 17 and 25 were enrolled, 14 mobilized an adequate number of CD133 + stem/progenitor cells and 12 were reinfused. No severe adverse events related to the procedure were reported. MELD score significantly worsened during mobilization in Child Turcotte Pugh-C patients. A significant improvement of liver function was observed 2 months after reinfusion (MELD 19.5 vs 16; P  = 0.045). Overall, 5 patients underwent liver transplantation within 12 months from reinfusion and 2 died because of progressive liver failure. Conclusions: CD133 + stem/progenitor cells reinfusion in patients with end-stage liver disease is feasible and safe. A worsening of liver function was observed during mobilization in Child Turcotte Pugh-C patients. The temporary improvement of MELD score after reinfusion suggests that stem cells therapy may be a "bridge to transplant" approach for these patients.